Experimental Investigation of the Shear Behavior of the Blind Rivet and Self-tapping Screw Hybrid Connection - Yunpeng CHU; Jinrong FU; Zhihao ZHONG; Xiaoqiang CHEN (工程科学与技术)
This study proposes a hybrid connection of pull rivets and self-tapping screws to address the defects in components connected by self-tapping screws, which are susceptible to pulling and causing severe damage to the structure during seismic activity, and enhance the anti-destruction capability of cold-formed thin-walled steel composite walls activity. This connection aims to mitigate the failure modes of self-tapping screws by analyzing the force transmission mechanism at the interlayer connection of composite walls. In this regard, a total of 48 sets of joint shear performance tests are conducted to evaluate the shear resistance of the hybrid connection. These tests include five common thicknesses of connection sheets in cold-formed thin-walled steel structures and a range of lap sheet thickness ratios from 1.0 to 2.0. The methods of connection tested are self-tapping screw connections, pull rivet connections and hybrid connections. Observations from the tests showed that hybrid connections prevent the pulling and tearing failures typically seen with self-tapping screws. The failure modes observed are predominantly sheet bearing failure, combined screw tilt failure, rivet shear failure, and partial shear combined with sheet bearing failure. Compared to single connection methods, the hybrid connection’ load-displacement curve demonstrates a longer plastic phase. When the thickness ratio exceeds 1.5 and the combined sheet thickness is under 3 mm, the load-carrying capacity and ductility of the hybrid connection increase significantly in comparison to the single connections. The calculated bearing capacity of the hybrid connection, using existing calculation methods, was found to be conservative when compared to the actual test results. The findings suggest that the hybrid connection can effectively counteract the weaknesses of blind rivets and self-tapping screws under shear stress, improve the resistance to pulling and tearing of self-tapping screws, and thus enhance the bearing capacity and ductility of the connection. Thickness and thickness ratio are key factors that influence the failure mode and bearing capacity of the hybrid connection. Furthermore, as the thickness ratio increases, so does the bearing capacity. The method of arrangement has a minimal impact on the mechanical performance and failure mechanism of hybrid connections. Under the experimental conditions of this study, based on the observed failure mode of the hybrid connection, an improved calculation method is proposed. This new method is based on existing calculation methods but provides more accurate results.